2019
DOI: 10.3389/fimmu.2019.01859
|View full text |Cite
|
Sign up to set email alerts
|

Fighting the Fire: Mechanisms of Inflammatory Gene Regulation by the Glucocorticoid Receptor

Abstract: For many decades, glucocorticoids have been widely used as the gold standard treatment for inflammatory conditions. Unfortunately, their clinical use is limited by severe adverse effects such as insulin resistance, cardiometabolic diseases, muscle and skin atrophies, osteoporosis, and depression. Glucocorticoids exert their effects by binding to the Glucocorticoid Receptor (GR), a ligand-activated transcription factor which both positively, and negatively regulates gene expression. Extensive research during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 222 publications
3
78
0
2
Order By: Relevance
“…NR3C1 usually exists in the cytoplasm and would be translocated to the nucleus after binding to its ligand. It could upregulate the anti-inflammatory protein or inhibit the expression of pro-inflammatory protein in the nucleus 59 . The significant downregulation of NR3C1 in the five organs may indicate an increased inflammatory response of various organs after SARS-CoV-2 infection.…”
Section: Cluster 4: Cytokinesmentioning
confidence: 99%
“…NR3C1 usually exists in the cytoplasm and would be translocated to the nucleus after binding to its ligand. It could upregulate the anti-inflammatory protein or inhibit the expression of pro-inflammatory protein in the nucleus 59 . The significant downregulation of NR3C1 in the five organs may indicate an increased inflammatory response of various organs after SARS-CoV-2 infection.…”
Section: Cluster 4: Cytokinesmentioning
confidence: 99%
“…Thus, it is possible that induction of Epo expression contributes to the resolution of inflammation. Similarly, increased levels of corticosteroids play an essential role in stress erythropoiesis, but glucocorticoid receptor signaling is also a potent anti-inflammatory signal [116]. Thus, Epo and corticosteroids represent signals that drive the proliferation and differentiation of SEPs and promote the resolution of inflammation.…”
Section: New Model: Stress Erythropoiesis Is a Key Component Of The Imentioning
confidence: 99%
“…Previous studies showed that Sp1, Egr-1, NFKB1, NR3C1 and PU.1 have been reported to play roles in inflammatory response [30][31][32][33][34], so we analyzed the mRNA levels of these transcription factors and found that, compared with those in control group, the mRNA levels of NFKB1, NR3C1 and Egr-1 were obviously lower in ALI group, while the mRNA levels of Sp1 and PU.1 significantly increased ( Figure 7E, P<0.05). Because the luciferase activity results showed that the putative transcription factors could negatively regulate MAPK4 expression and accumulating evidences have shown that NFKB1 and NR3C1 were anti-inflammatory genes [31,32], so we presumed that NFKB1 and NR3C1 might be critical transcription factors in regulating MAPK4 expression in ALI. Expectedly, further analysis showed that the protein levels of NFKB1 and NR3C1 decreased obviously in lung tissues in ALI mice ( Figure 7F, P<0.05), which is consistent with our above data.…”
Section: Nfkb1 and Nr3c1 Negatively Regulate The Expression Of Mapk4mentioning
confidence: 83%